FMR1 deletion in rats induces hyperactivity with no changes in striatal dopamine transporter availability - Annunziata D’Elia; Sara Schiavi; Antonia Manduca; Alessandro Rava; Valeria Buzzelli; Fabrizio Ascone; Tiziana Orsini; Sabrina Putti; Andrea Soluri; Filippo Galli; Alessandro Soluri; Maurizio Mattei; et al. (Scientific Reports, 2022)
Abstract Autism Spectrum Disorder (ASD) is a pervasive neurodevelopmental disorder emerging in early life characterized by impairments in social interaction, poor verbal and non-verbal communication, and repetitive patterns of behaviors. Among the best-known genetic risk factors for ASD, there are mutations causing the loss of the Fragile X Messenger Ribonucleoprotein 1 (FMRP) leading to Fragile X syndrome (FXS), a common form of inherited intellectual disability and the leading monogenic cause of ASD. Being a pivotal regulator of motor activity, motivation, attention, and reward processing, dopaminergic neurotransmission has a key role in several neuropsychiatric disorders, including ASD. Fmr1 Δ exon 8 rats have been validated as a genetic model of ASD based on FMR1 deletion, and they are also a rat model of FXS. Here, we performed behavioral, biochemical and in vivo SPECT neuroimaging experiments to investigate whether Fmr1 Δ exon 8 rats display ASD-like repetitive behaviors associated with changes in striatal dopamine transporter (DAT) availability assessed through in vivo SPECT neuroimaging. At the behavioral level, Fmr1 Δ exon 8 rats displayed hyperactivity in the open field test in the absence of repetitive behaviors in the hole board test. However, these behavioral alterations were not associated with changes in striatal DAT availability as assessed by non-invasive in vivo SPECT and Western blot analyses.